Respuesta :
(6x^3-2x^2+4) - (2x^3+4x^2-5)
Subtract the like terms
6x^3 - 2x^3 = 4x^3
-2x^2 - 4x^2 = -6x^2
4 - (-5) = 9
The final answer would be
4x^3 - 6x^2 + 9
Subtract the like terms
6x^3 - 2x^3 = 4x^3
-2x^2 - 4x^2 = -6x^2
4 - (-5) = 9
The final answer would be
4x^3 - 6x^2 + 9
Answer:
D) 4x^3 -6x^2 + 9
Step-by-step explanation:
Given: 6x^3-2x^2+4) - (2x^3+4x^2-5)
Distribute the negative sign, we get
6x^3 -2x^2 + 4 -2x^3 -4x^2 + 5
Now combine the like terms and simplify.
= 6x^3 -2x^3 -2x^2 -4x^2 + 4 +5
= 4x^3 -6x^2 + 9
Answer: D) 4x^3 -6x^2 + 9
Hope this will helpful.
Thank you.